The mental health crisis in global higher education: understanding and mitigating academic load stress among international students from Asia and Africa in Nanjing China - Suyuhan, Wang; Khoso, Abdul Rasool; Jintu, Gu; Bhutto, Shahnaz (Frontiers in Psychology, 2026)
The mental health challenges faced by international students in higher education institutions worldwide have reached critical levels, with academic stress identified as a primary contributing factor. This study investigates the psychological effects of academic load stress on international students in Nanjing, China, emphasizing the complex interaction between cultural, academic, and social stressors. Employing a mixed-methods design, the research integrates quantitative surveys (n = 1,115) with qualitative interviews (n = 10) to analyze stress triggers, mental health outcomes, and institutional support mechanisms. Key results indicate 40% of participants experienced frequent stress symptoms. Hierarchical regression analysis identified academic workload as the strongest predictor for stress (β = 0.37, p < 0.001), anxiety (β = 0.33, p < 0.001), and depression (β = 0.29, p < 0.001), with the full model explaining a significant portion of variance (Total R2 = 0.154 for stress, ΔR2 = 0.102 for academic factors). Social isolation and language barriers were also significant contributors across all mental health outcomes. Stress levels varied by program, with Master’s students reporting the highest prevalence of moderate stress (48%) and PhD candidates the highest severe stress (45%). Qualitative data revealed cultural adaptation difficulties, including challenges with Confucian educational norms and language proficiency, which intensified stress. Despite existing support services, only 38% of students utilized counseling, citing stigma and cultural misalignment as barriers. This study highlights the urgent need for tailored interventions, such as culturally responsive faculty training, peer support networks, and improved mental health resources. By contextualizing global research within China’s higher education landscape, the findings advance understanding of academic stress and propose practical strategies to enhance student well-being in international academic environments.